Analisis Formulasi Kebijakan Program Revitalisasi Pasar Besar Kota Pasuruan Tahun 2022 - Mariana Irbach Khonsa R; Tauran Tauran; Indah Prabawati; Ahmad Nizar Hilmi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the policy formulation process for the Pasar Besar revitalization program in Pasuruan City, focusing on the stages involved in policy formulation. This study uses a descriptive qualitative approach with interviews with informants and documentation. The results of the study reveal that the Pasar Besar revitalization policy formulation process does not fully conform to the four ideal stages. Of the four stages that should be followed: problem formulation, agenda process, alternative formulation, and policy determination, only two stages were carried out by policy makers in policy formulation, namely problem definition and policy determination. The results of the study reveal that at the problem definition stage, the Department of Industry and Trade defines the main problem as damage and unsuitability of market facilities and infrastructure, which has reached 70 percent, thus not complying with the Indonesian National Standard (SNI) for traditional markets. At the policy-making stage, the program is established and implemented through the 2022 Regional Work Plan (RKPD) of the Department of Industry and Trade, with funding provided through financial assistance to the provincial government. Several issues related to the market revitalization program policy formulation process include: the need to expand policy alternatives into several alternative options, such as considering partial or total market revitalization, and the need for alternative marking, such as gradual revitalization or making small but consistent improvements.